Combined effect of tetracycline and copper ion on catalase activity of microorganisms during the biological phosphorus removal. (15th February 2022) - Man, Yacan; Zhang, Hua; Huang, Jian; Xi, Shanshan; Wang, Jinhua; Tao, Haitao; Zhou, Yu
Abstract: Microbial catalase is a key enzyme that affects the activities of microorganisms, and the catalase activity is affected by pollutants in wastewater. However, the effects of mixed pollutants on catalase activity are rather complex. To reveal the effect of the mixed pollutants on catalase activity of microorganisms, the present study investigated tetracycline and copper ion as pollutants during the biological phosphorus removal. Three concentration ratios of tetracycline and copper ion and 27 different concentration gradients were designed through the direct equipartition ray and the dilution factor method. The effects of mixed pollutants on the catalase activity of microorganisms were analyzed by the nonlinear regression equation and concentration-addition model. The results showed that, with the increase of actuation duration and the pollutant concentration, the inhibitory effects on the catalase activity of microorganisms obviously increased, which indicated that the inhibitory effects are concentration-dependent and time-dependent. The concentration-addition model suggested that when the ratio was 0.297, the combined effect of mixed pollutants on the activity of microbial catalase was mainly antagonism. When the ratio is 0.894, the combined effect was mainly additivity. When the ratio was 2.676, the combined effect transformed from synergism to additivity and antagonism. The study of the combined effects of tetracycline and copper ion on the catalase activity is helpful to further study their ecotoxicological mechanisms in wastewater treatment. Highlights: Effects of tetracycline and copper ion on catalase activity were researched. Inhibitory effects increased with concentration-dependent and time-dependent. Combined effects of mixed pollutants on catalase activity were first characterized. Combined effects changed with concentration ratios of pollutants and reaction time.